Pengaruh Motivasi Kerja dan Knowledge Management Terhadap Produktivitas Kerja Karyawan Konveksi Sepatu dan Sandal XYZ Bandung - Tjahjawati, Sri Surjani; Firmansyah, Yayan (Sekolah Tinggi Ilmu Ekonomi Riau, 2020)
This research was conducted at the Cibaduyut XYZ shoe industry center, a company engaged in the SME sector of the leather shoes and sandals. Based on preliminary survey,Â company XYZ is an industry of making shoes and leather sandals with active work competence and includes a creative industry that promoted by the government.The purpose of this study is to increase work motivation on work productivity, knowledge management on work productivity and simultaneous work motivation and knowledge management on work productivity. Used Verivication methodThe results showed that work motivation was positive and significant to work productivity by 14.9%, while management knowledge affected positively and significantly to work productivity by 5.3%. While work motivation and knowledge management are positive and significant at 16.81%.Based on results,Â entrepreneurs need to provide stimulus to improve productivity with rewards and penalties, such as giving bonuses to companies that reach their targets and other rewards. to continue improving the sustainability of entrepreneurs it is necessary to increase the sustainability of knowledge and experience especially models of shoes and sandals. The next researcher needs to report other variables such as human capital, ROTI (return on investment in training) and other relevant themes